Dynamic Positron Emission Tomography Imaging of Renal Clearable Gold Nanoparticles. Issue 20 (9th April 2016) - Chen, Feng; Goel, Shreya; Hernandez, Reinier; Graves, Stephen A.; Shi, Sixiang; Nickles, Robert J.; Cai, Weibo
Abstract : Optical imaging has been the primary imaging modality for nearly all of the renal clearable nanoparticles since 2007. Due to the tissue depth penetration limitation, providing accurate organ kinetics non‐invasively has long been a huge challenge. Although a more quantitative imaging technique has been developed by labeling nanoparticles with single‐photon emission computed tomography (SPECT) isotopes, the low temporal resolution of SPECT still limits its potential for visualizing the rapid dynamic process of renal clearable nanoparticles in vivo. The dynamic positron emission tomography (PET) imaging of renal clearable gold (Au) nanoparticles by labeling them with copper‐64 ( 64 Cu) to form 64 Cu‐NOTA‐Au‐GSH is reported. Systematic nanoparticle synthesis and characterizations are performed to demonstrate the efficient renal clearance of as‐prepared nanoparticles. A rapid renal clearance of 64 Cu‐NOTA‐Au‐GSH is observed (>75%ID at 24 h post‐injection) with its elimination half‐life calculated to be less than 6 min, over 130 times shorter than previously reported similar nanoparticles. Dynamic PET imaging not only addresses the current challenges in accurately and non‐invasively acquiring the organ kinetics, but also potentially provides a highly useful tool for studying renal clearance mechanism of other ultra‐small nanoparticles, as well as the diagnosis of kidney diseases in the near future. Abstract : Dynamic positron emission tomography imaging of radio‐labeled ultra‐small gold nanoparticles is reported to quantitatively and non‐invasively study the pharmacokinetics of nanoparticles in major organs. A rapid renal clearance of as‐synthesized nanoparticles is observed with its elimination half‐life calculated to be >130 times shorter than previously reported similar nanoparticles.